2004
DOI: 10.1081/ada-120029872
|View full text |Cite
|
Sign up to set email alerts
|

The 3‐Metros Study of Drugs and Crime in South Africa: Findings and Policy Implications

Abstract: This study examined the drug-crime nexus by investigating the prevalence of recent drug use among persons arrested by the police. Data were gathered during August/September 2000 from 1050 adult arrestees in eight police stations in Cape Town, Durban, and Johannesburg (South Africa). Measures included urinalysis results for cannabis, methaqualone (Mandrax), opiates, cocaine, amphetamines, and benzodizepines, and a questionnaire designed to assess socioeconomic and demographic backgrounds of arrestees, history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…Nevertheless, one local study showed self-reported cannabis use at between 22% and 28% of arrestees who committed violent offences [42] and another conducted among arrestees for violent crimes across eight police stations in Cape Town, Durban and Johannesburg confirmed a high prevalence of drug usage amongst the alleged perpetrators, with nearly half (45%) testing positive for illicit drugs by urinalysis [43]. Arrestees in Cape Town tested positive for Mandrax, which may be attributed to gang activities in the city [44].…”
Section: Behavioural Factorsmentioning
confidence: 99%
“…Nevertheless, one local study showed self-reported cannabis use at between 22% and 28% of arrestees who committed violent offences [42] and another conducted among arrestees for violent crimes across eight police stations in Cape Town, Durban and Johannesburg confirmed a high prevalence of drug usage amongst the alleged perpetrators, with nearly half (45%) testing positive for illicit drugs by urinalysis [43]. Arrestees in Cape Town tested positive for Mandrax, which may be attributed to gang activities in the city [44].…”
Section: Behavioural Factorsmentioning
confidence: 99%
“…While there may be an ever-growing literature on the multiple and diverse impacts of illegal substances on individuals, communities and South African society as a whole, 8 there is little empirical information on the illegal substance economy itself. What does exist invariably focuses on public health concerns, such as treatment centre data, and does not engage with the criminal economy itself.…”
Section: This Article Documents and Contextualises Fluctuations In Thmentioning
confidence: 99%
“…On the first issue, our own research has shown associations between cannabis use and road traffic injuries and other forms of trauma, [6] crime, particularly property crime and murder, [7] and sexual HIV risk behaviours, [8] but the causal mechanisms were not clearly elucidated. Unpublished research conducted in SA using functional magnetic resonance imaging also showed cognitive deficits associated with cannabis use, even after participants had stopped using cannabis for several weeks (Carey P, et al …”
Section: Harms Associated With Cannabis Usementioning
confidence: 99%